DNA damage in Wistar rats exposed to dithiocarbamate pesticide mancozeb - Goldoni, A; Klauck, C R; Da Silva, S T; Da Silva, M D; Ardenghi, P G; Da Silva, L B (Folia biologica, 2014)
Pesticides are used in large amounts in agriculture and the evaluation of their toxic effects is of major concern to public and environmental health. The aim of the present study was to investigate the genotoxic potential of a commercial formulation of the fungicide mancozeb by the micronucleus test in bone marrow and the comet assay in total blood of Wistar rats. Adult male Wistar rats were treated with a solution of mancozeb at a concentration of 40 mg/kg/day, administered intraperitoneally for 18 consecutive days, and compared to a control group. The results indicate that mancozeb induced significantly higher DNA damage as detected by the comet assay and increased the frequency of micronuclei. The results show that mancozeb is genotoxic and may adversely affect the DNA integrity of exposed organisms.
Keywords: Animals; Micronuclei, Chromosome-Defective; DNA Damage; maneb; Rats, Wistar; Micronucleus Tests; zineb; erytrocyty; Maneb; Zineb; poškození DNA; mikrojaderné testy; Male; Erythrocytes; Ditiocarb; zvířata; mužské pohlaví; mikrojádra chromozomálně defektní; dithiokarb; počet erytrocytů; potkani Wistar; Erythrocyte Count